Ensino jurídico como atividade especializada do aparelho ideológico escolar - Salles, Luiz Caetano de (2014)
Based on the Theory of Ideological State Apparatuses put forth by philosopher Louis Pierre Althusser and instigated by the contradictions between the rapid growth in the last two decades the number of courses of legal education and Bachelors they launched on the labor market as operators of the Law (which is based on liberal discourse of equality and freedom) and the inalterability of discrimination and oppression within the Brazilian society, this study uses the method of historical materialism dialectic to analyze the peculiarities of legal education and with this remove the varnish ideological that gives brightness to this type of education, revealing, in the end, merely as a specialized activity of the school ideological apparatus attesting to the state of potential operators of its repressive apparatus, whose primary function an ulterior motives are to ensure the reproduction of the relations of production of the capitalist mode of production.